Concepts of fitness and wellness : (McGraw-Hill, 2006)
This trusted text provides readers with the self-management skills necessary to adopt a healthy lifestyle; enhanced by the use of the activity labs and logs also included, these skills will make a positive difference in the readers' health, fitness, and wellness. The text's proven conceptual format (offering brief "concepts" rather than chapters) presents information in a useful and concise way, and its focus on “process” or lifestyle changes, with early coverage of planning, enables students to apply the concepts immediately. It is one of three Concepts texts now available at the same time, each offering a distinct topical emphasis.